Statics and dynamics structural analysis of a 4.5 ton truck chassis - Teo, Han Fui; Abd. Rahman, Roslan (Faculty of Mechanical Engineering, 2007)
Truck chassis forms the structural backbone of a commercial vehicle. The main function of the truck chassis is to support the components and payload placed upon it. When the truck travels along the road, the chassis is subjected to vibration induced by road roughness and excitation by vibrating components mounted on it. This paper presents the study of the vibration characteristics of the truck chassis that include the natural frequencies and mode shapes. The responses of the truck chassis which include the stress distribution and displacement under various loading condition are also observed. The method used in the numerical analysis is finite element technique. The results show that the road excitation is the main disturbance to the truck chassis as the chassis natural frequencies lie within the road excitation frequency range. The mode shape results determine the suitable mounting locations of components like engine and suspension system. Some modifications are also suggested to reduce the vibration and to improve the strength of the truck chassis.